Formal Model of Informatics Undergraduate Curriculum in Petri Nets - Aditya Bagoes Saputra (PPM Institut Teknologi Telkom Telkom Jakarta, 2022)
The academic system in the undergraduate program of Informatics, Bandung Telkom Institute of Technology (now Telkom University) defines rules and procedures of curriculum and study program, evaluation of study, academic council, counseling, and registration. The curriculum and study program explain the courses. This paper develops formal model and model analysis of this curriculum in Petri nets. The result of this is the Petri nets model and its analysis to check properties based on the courses and curriculum. The course prerequisite model and curriculum follow the academic system, not deadlocked, and not reversible.